Integrating English with total physical response as an effective method for preschoolers cognitive development (IR) - Krishnavani Anmal Govindan Nair (2018)
This qualitative naturalistic observational study explores integrating English with Total Physical Response (TPR) for preschoolers’ cognitive development. Research is built upon, review of cognitive developmental theorists, stakeholders, teachers’ feedback with researcher’s empirical knowledge and experience. The right and left brain coordination in cognitive development provides a unifying perspective for this research. In order to accentuate the TPR curriculum, conducive, learning environments, teaching tools and competent teachers are necessary complements to dual-hemisphere collaboration for cognitive development. Qualitative observation of 5 years old, 10 participants’ cognitive attributes, through participants’ response and perspectives towards this teaching-learning approach justified findings pertinent to research questions. Through this research it has been found that participants are actively engaged in the learning process 50% longer than traditional teaching approaches. Participants’ also qualitatively based on third-party teacher feed-back, showed increased capability in participants ability to compose short, meaningful sentences, increased adoption and use of vocabulary, as well as increased motivation towards learning. The implication of this research indicates that progressions in language also translated to improved observable cognitive output such as the ability to respond to questions, asking questions to clear doubts, justified thoughts and opinions, as well as increased attention, retention and recall of knowledge